PENYEBAB GURU TIDAK MENGGUNAKAN RPP DALAM PEMBELAJARAN (Studi SMA Negeri 1 Bunut Kecamatan Bunut Kabupaten Pelalawan Provinsi Riau) - Arna, Arna; Maihasni, Maihasni; Elvawati, Elvawati (Pendidikan Sosiologi, 2014)
Lesson plan is an estimate or projection teachers about the activities that will be undertaken by the teachers and learners, especially in conjunction with the formation of competencies and learning goals achievement. Lesson plan serves as a guide and reference for teachers and students in learning activities in the classroom to be more directed . The statement is found in the field, Lesson plan only serves as a complementary administrative and simply complement the teacher when there are reviews from watchdogs to see fittings team teaching tool . The purpose of this study was to find out the cause of non-performance of the learning activities are planned according to the lesson plan .          To clarify this paper the authors use the theory Vygostky kontruktivisme theory ( knowledge ) . Assume that a person should know means to know something, this means that one can learn something new if it can explain the elements that develop something . So a teacher should know what the lesson plan then able to make and understand what measures will be implemented learning activities in the classroom, if it does not make or do not understand , then the result is the delivery of learning activities appropriate to the Draft .         The type of descriptive qualitative research . Informant selection techniques done by purposive sampling with 17 informants . Methods for collecting data in this study using observation and interviews . Uni analysis in the study is the individual . The analysis performed in this study using the interactive developed by Miles and Huberman .          The results showed that the cause of non-performance in -class learning activities are planned according to the lesson plan is because 1 ) Lesson plan planned by others , 2 ) focus in prioritizing teachers approval of XII grade students , 3 ) Limitations hour lesson , 4 ) Depending on the situation and conditions from a supervisor , 5 ) curriculum changes , 6 ) media learn less , 7 ) resources to learn .